2021
DOI: 10.1136/bmjdrc-2021-002263
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-glycome shows continuous deterioration as the diagnosis of insulin resistance approaches

Abstract: IntroductionPrediction of type 2 diabetes mellitus (T2DM) and its preceding factors, such as insulin resistance (IR), is of great importance as it may allow delay or prevention of onset of the disease. Plasma protein N-glycome has emerged as a promising predictive biomarker. In a prospective longitudinal study, we included patients with a first diagnosis of impaired glucose metabolism (IR or T2DM) to investigate the N-glycosylation’s predictive value years before diabetes development.Research design and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Thus, we explored the N-glycan traits whose expression were different in cases and controls. The present study validates that of Cvetko et al 36 and Clemens et al 35 , we identified GPs 34, 32, 26, 31, 36 and 30 to be highly expressed in T2DM in the first principal axis and on the second principal axis, GPs 38, 1, 2, 25 and 20 were dominant in T2DM. Sialylated glycans (GP26, GP32, GP35 and GP36) are expressed on a1-acid glycoprotein, whereas GP18 and GP20 originates from glycoproteins a-antitrypsin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, we explored the N-glycan traits whose expression were different in cases and controls. The present study validates that of Cvetko et al 36 and Clemens et al 35 , we identified GPs 34, 32, 26, 31, 36 and 30 to be highly expressed in T2DM in the first principal axis and on the second principal axis, GPs 38, 1, 2, 25 and 20 were dominant in T2DM. Sialylated glycans (GP26, GP32, GP35 and GP36) are expressed on a1-acid glycoprotein, whereas GP18 and GP20 originates from glycoproteins a-antitrypsin.…”
Section: Discussionsupporting
confidence: 93%
“…First, the GST2D score was used to predict T2DM development 6–8 years before clinical manifestation 35 . In another study, Cvetko et al 36 reported that individuals who were healthy at baseline but developed insulin resistance and T2DM over time, were characterised by complex and highly branched N-glycan structures. Specifically, the study identified alterations in eight N-glycans: GP10, GP16, GP18, GP19, GP20, GP26, GP32 and GP34 36 ; with GP 32 and GP34 being the most significant in the continuum of insulin resistance and T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated glycan changes in various disorders, such as inflammation, aging, cancer, autoimmune diseases [ 9 11 ]. Studies have reported glycans as very responsive to mentioned conditions, sometimes even years before its onset [ 12 , 13 ], making glycans powerful potential biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides serving constructive, storing, or protective roles, with evolution, glycans became increasingly more complex and began to acquire other functional roles crucial for complex organisms ( Lauc et al, 2014 ). Improper glycosylation underlies many diseases ( Freeze, 2006 ) and some glycans may be used as novel predictive or diagnostic biomarkers for some of them ( Cvetko et al, 2021 ). Therefore, it is important to include high-throughput glycan analysis in different studies to have a complete picture of what is happening.…”
Section: Introductionmentioning
confidence: 99%